Splenosystemic Shunts in Cats: A Retrospective of 33 Cases (2004–2011). (10th September 2013) - Palerme, J‐S.; Brown, J.C.; Marks, S.L.; Birkenheuer, A.J.
<x xml:space="preserve">Abstract</x> Background Portosystemic shunts are uncommonly reported in cats. The majority of reports describe congenital shunts in young cats originating from the left gastric vein. Although they are only rarely reported, acquired portosystemic shunts in cats appear to be more variable in their anatomic location. Hypothesis/Objective To describe the signalment and disease conditions found in cats with splenosystemic shunts. Animals Thirty‐three client‐owned cats with documented splenosystemic shunts. Materials and Methods Retrospective study. All cats with vascular communications between the splenic and left renal veins or the splenic vein and caudal vena cava diagnosed ultrasonographically between 2004 and 2011 were included. Collected data included age, breed, sex, presenting complaints, clinicopathologic data, as well as clinical diagnosis when available. Results Splenosystemic shunts were identified in 1.3% of the cats that had an abdominal ultrasound performed during the study period. Older, spayed female cats were found to be significantly overrepresented when compared with the total population of cats having undergone ultrasound over the same time period. A large proportion of cats (42%) had a hepatopathy with the potential for associated portal hypertension. Conclusions and Clinical Importance Neither the signalment of cats in this report nor the anatomy of their portovascular anomalies shared similarities with those cats previously identified with single‐vessel shunts. The relevance and etiology of these newly described splenosystemic shunts remain elusive and warrantsfurther investigation.